CONSTITUTIONAL ENSHRINEMENT OF THE RIGHT TO APPEAL TO INTERNATIONAL HUMAN RIGHTS BODIES: FOREIGN PRACTICE - Almassuly, Арлан; Abaideldinov, Ербол Мусинович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2025)
The scientific article presents a study of the practice of constitutional enshrinement of the right to appeal to international human rights bodies in a number of states, the development of this constitutional norm within domestic law, and the interaction of states with international human rights bodies. The study includes a comparative analysis of the implementation practices of decisions made by international human rights bodies in states where the right to appeal to these bodies is constitutionally enshrined and those where it is not. Based on the analysis, a conclusion is drawn about the effectiveness of constitutional enshrinement of the right to appeal to international human rights bodies as a political and legal guarantee that ensures the consideration and implementation of decisions made by these bodies. The article also examines theoretical and practical aspects of the implementation of the right to appeal to international human rights bodies. Additional patterns arising from the constitutional enshrinement of this right have been identified. In conclusion, the article formulates the main finding of the study, which states that the constitutional enshrinement of the right to appeal to international human rights bodies reflects the political stance of a state genuinely committed to ensuring and protecting human rights within its territory. Furthermore, it has been revealed that this approach enhances the realization of the right, particularly through raising citizens’ awareness and improving the state’s regulatory framework.